Dahlia Inulin and Lactobacillus sp. in Step Down Protein Diet on Villi Development and Growth of KUB Chickens - S. A. Purbarani; H. I. Wahyuni; N. Suthama (Faculty of Animal Science, Bogor Agricultural University, 2019)
The research was aimed to evaluate the inclusion effect of dahlia tubers inulin (DTI) combined with Lactobacillus sp. in dietary protein step down on villi development and growth of KUB chicken. The experiment was arranged in a completely randomized design using 160 birds of one-day-old KUB chicks (body weight was 26.32±1.19 g) divided into 5 treatments with 4 replications. The treatment applied were: (1) P180S: ration with 18% protein with the addition of 1.2% DTI and 1.2 mL (108 cfu/mL) Lactobacillus sp. provided since one-day-old, (2) P15: ration with 15% protein without DTI and Lactobacillus addition and was given from 8-day old, (3) P18: ration with 18% protein without DTI and Lactobacillus addition and was given from 8-day old, (4) P15S: ration with 15% protein with the addition of 1.2% DTI and 1.2 mL Lactobacillus sp. offered from 8-day old, and (5) P18S: ration with 18% protein with the addition of 1.2% DTI and 1.2 mL Lactobacillus sp. offered from 8-day old. The experimental birds allocated in the treatments 2 to 5 were fed ration with 21% protein from hatching until 7-day old. Variables observed were the jejunal pH, total Coliform and lactic acid bacteria (LAB), villi height, protein digestibility, final body weight, and carcass percentage. Data were subjected to analysis of variance (ANOVA), and followed by orthogonal contrast test. Orthogonal contrast test showed that feeding 18% dietary protein fortified with a combination of 1.2% inulin dahlia tuber and 1.2 mL Lactobacillus sp. given since one-day-old significantly (P<0.05) affected the height of jejunal villi, protein digestibility, carcass percentage, final body weight, jejunal pH, and Coliform number. In conclusion, feeding 18% dietary protein fortified with a combination of 1.2% of inulin dahlia tuber and 1.2 mL of Lactobacillus sp. since one-day-old increases the height of the jejunum villi and growth of KUB chicken.